Price Discrimination and the Location Choice of a Durable Goods Monopoly - Paolo Garella (Alma Mater Studiorum - Università di Bologna, Dipartimento di Scienze Economiche (DSE), 1997)
The traditional analysis of the location choice by a monopoly has been developed thinking of static monopolies, namely monopolies selling non-durable goods. At the same time, the spatial approach has been widely used in applications to the choice of product design. In a spatial context, the question is if monopoly power leads to the plant location which minimizes transport costs. In terms of product characteristics the question is whether a monopoly will produce the variety which maximizes the social welfare—I do not treat here the case of multiplant and multiproduct monopoly. The definition of product specification by way of spatial models, following Hotelling (1931), is usually one of horizontal differentiation, where the consumers do not unanimously rank the different specifications of a good footnote .
Keywords: 330